The Role of Building a Strong Sports Country in Improving the Psychological Health of Adolescents from the Perspective of Marxism - Xiaodong Kong; Aijun Liu; Kun Hou (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to understand the role of building a strong sports country in improving the mental health of adolescents, a study on the role of building a strong sports country in improving the mental health of adolescents from a Marxist perspective has been proposed. In this study, 436 college students were selected and divided into the Dance sport exercise group and the sedentary group. The participants were measured using the "Physical Exercise Level Scale", the "Multi-dimensional Assessment Questionnaire for Adolescent Health", and the "Coping Style Scale for College Students". Covariance analysis was used to test the difference between groups, and structural equation model and Sobel test were used to analyse the Mesomeric effect. The results showed that there were significant differences in the scores of question orientation, emotional orientation and avoidance orientation between the Dance sport group and the sedentary group (P<0.05). In the dimensions of mental Suboptimal health emotional problems and social adaptation problems, the scores of the Dance sport group and the sedentary group were also statistically significant (P<0.05). The dimension of problem orientation in coping style acts as a mediating variable between whether to participate in Dance sport exercise and the dimension of mental suboptimal health emotional problems and shows a partial mediating role. Participation in Dancesport exercise can enable college students to adopt more positive coping styles and have better mental health. Through systematic Dance sport training, college students can take a positive way to deal with problems, thus promoting them to have a more positive emotional experience.